2018
DOI: 10.1021/acsami.8b13793
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Protein Surfaces Enabled by Plant-Based Polyphenol Coatings

Abstract: Proteins represent complex biomolecules capable of wide-ranging but also highly specific functionalities. Their immobilization on material supports can enable broad applications from sensing and industrial biocatalysis to biomedical interfaces and materials. We demonstrate the advantages of using aqueous-processed cross-linked polyphenol coatings for immobilizing proteins, including IgG, avidin, and various single and multidomain enzymes on diverse materials, to enable active biofunctional structures (e.g., ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Abouelmagd et al addressed that coating TA onto poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles allowed the particles to remain optically inert, facilitating the secondary functionalization of various ligands, small fluorescent dyes, folate‐conjugated and amine‐terminated polymers, proteins, and polysaccharides . A previous study also demonstrated the pyrogallol‐mediated postimmobilization of a variety of proteins, such as acid phosphatase, chymotrypsin, horseradish peroxidase, lactate dehydrogenase, and immunoglobulin G (IgG) . In conclusion, to achieve high biological activities in protein immobilization, 1) the optimization of the pH in the coating of a pyrogallol‐containing molecule and 2) the subsequent immobilization of proteins are required.…”
Section: Surface Engineering Strategies Using Pyrogallol Materialsmentioning
confidence: 99%
“…Abouelmagd et al addressed that coating TA onto poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles allowed the particles to remain optically inert, facilitating the secondary functionalization of various ligands, small fluorescent dyes, folate‐conjugated and amine‐terminated polymers, proteins, and polysaccharides . A previous study also demonstrated the pyrogallol‐mediated postimmobilization of a variety of proteins, such as acid phosphatase, chymotrypsin, horseradish peroxidase, lactate dehydrogenase, and immunoglobulin G (IgG) . In conclusion, to achieve high biological activities in protein immobilization, 1) the optimization of the pH in the coating of a pyrogallol‐containing molecule and 2) the subsequent immobilization of proteins are required.…”
Section: Surface Engineering Strategies Using Pyrogallol Materialsmentioning
confidence: 99%
“…Physical adsorption may be facile, but the amount immobilized may be low, and desorption can be an issue. 6 Chemical activation may increase surface coupling but traditionally requires aggressive reagents 43 (thus, other fabrics, e.g., polyesters, are also being considered). 44,45 Enhanced protein immobilization through coatings of polymer brushes or hydrogel layers involves additional chemical steps.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] They do not discolor the substrate and are much lower in cost compared with polydopamine. 6,50 However, our recent work also showed that their chemical properties and the activity of proteins immobilized on them could vary depending on the substrate material. 6 In this report, we have therefore studied how the combination of poly(tannic acid) (PTA) and SNPs may modify the nal immobilized antibody activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost of dopamine may be prohibitive for the broad applications of such derived MCMs. In addition, it takes quite a long time to deposit PDA coating, typically no less than 12 h. More recent expansions of catechol chemistry‐based coatings have bred the polyphenol coating . In this respect, tannic acid (TA) is the most broadly used polyphenol due to its easy acquisition and low cost.…”
Section: Introductionmentioning
confidence: 99%